Evidence that twinning rate in Malpnra sheep is not linked with Booroola fecundity (FecB) gene - Kumar, Satish; Kolte, Atul P; Mishra, A K; Singh, V K (The Indian Journal of Animal Sciences, 2011)
Malpura sheep were screened for FecB mutation and its possible linkage with twinning if ·any. All ewes were found homozygous non-carrier (FecB-t+) for Booroola mutation; the FeeB gene was present in Malpura sheep but does not carry mutation. Study revealed that twinning in Malpura ewes is not linked with mutation in Booroola fecundity gene.